Influence of Additive Manufacturing Process on the Fatigue of Polymer Materials: A Review - OTSUPIUS, Enakhe P.; ACHEKUOGENE, Nihad (FUDMA Journal of Engineering and Technology, 2026)
Rapid prototyping has given way to the creation of useful end-use components using Additive Manufacturing (AM), also referred to as three-dimensional (3D) printing. However, the intrinsic layer-by-layer fabrication process results in anisotropic mechanical characteristics and structural flaws that greatly influence the fatigue life of polymer materials. Different parameters affect the fatigue life of a polymer material and subsequently their mechanical properties. In this review, AM process parameters such as build orientation, raster angle, layer thickness and material used are examined, the proper selection of process parameters has an overall impact on the strength of 3D-printed components. This paper offers insights into these process parameters by summarizing recently reported research.